Family burden among caregivers of patients with chronic mental disorders - Sateesh Rangarao Koujalgi; Raghavendra Bheemappa Nayak (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Caregivers play an important role in dealing with people with chronic mental disorders. Rates of caregiver burden are high and it increases the risk of caregiver depression and health problems. Therefore, an in-depth study is needed to understand the burden faced by primary caregivers of patients suffering from chronic mental disorders. AIM: The aim of the study is to examine the burden borne by families of individuals suffering from chronic mental disorders. MATERIAL AND METHODS: From the caregivers of patients with chronic mental disorders some were chosen. It is a cross sectional study. Purposive sampling technique has been adopted. Patients were diagnosed as having mental disorders using International Classification of Disease -10, classification of Mental and Behavioral Disorders, Diagnostic Criteria for Research ICD-10 criteria. Pollack and Perlick scale was used to identify the key family caregivers. Patients with two or more than two-year duration of illness were included in the study group. RESULTS: Caregivers of patients with chronic mental disorders experienced considerable high degree of family care burden. CONCLUSION: The study finds that a high burden is borne by caregivers of patients suffering from chronic mental disorders.